Tailoring of the interface morphology of WS2/CrN bilayered thin film for enhanced tribological property. (October 2018) - Wang, Desheng; Hu, Ming; Gao, Xiaoming; Jiang, Dong; Fu, Yanlong; Weng, Lijun; Sun, Jiayi
Abstract: The WS2 /CrN bilayered films with different interface morphologies between WS2 and CrN layer were prepared by physical vapor deposition. By controlling the deposition parameters, the surface of CrN interlayer exhibited compact granular structure when deposited under low partial pressure of Ar while a cone array-like surface appeared under high Ar partial pressure. The surface texture of the CrN interlayer had a great effect on the tribological performance of the WS2 /CrN film. The compact CrN textured WS2 film exhibited a wear life about 2.6 × 10 5 cycles while the optimal cone array-like CrN textured WS2 film showed a much longer wear life reaching to 6.8 × 10 5 cycles, which was more than 2.6 times of that for compact CrN textured WS2 film and 3.5 times of that for WS2 film without the CrN interlayer. The improved tribological property of the optimal cone array-like CrN textured WS2 film was attributed to the high adhesion between the WS2 layer and the CrN interlayer. Meanwhile, the reservoir and replenishment of the WS2 lubricant by the CrN nanocones during the friction made a significant contribution for the long wear life. Highlights: Compact and cone array-like CrN interlayers were deposited under different Ar partial pressure. Different tribological performances would be resulted by tailoring the interface of WS2 /CrN bilayered film. The reservoir and replenishment of the WS2 lubricates by CrN nanocone array contribute to the tribological performances.